Arrangement and Description of Music Manuscripts and Scores: An Example of Taiwanese Composer LAI Deh-Ho’s Collection - Tzu-Chia Tseng (Tūzī yǔ dàng’àn xuékān, 2021)
Music is the art of sound and needs to be preserved with music notation. Over the centuries, a large number of musical works have been accumulated. Due to their particularity and uniqueness, the various music manuscripts and scores composed during the creative stage have to be completely preserved, arranged and described. This article intends to start with the perspective of archival studies, through combing the standards of music materials’ classification and arrangement, as well as the description of the content based on the “Describing Archives: A Content Standard” (DACS), then takes the Taiwanese composer LAI Deh-Ho’s collection as an example, carries out the empirical analysis and puts forward the conclusions and suggestions. This article is expected to be helpful to the research of music archives in Taiwan and even in the Chinese-language regions.